DETERMINASI KEPATUHAN MENUNAIKAN ZAKAT MAAL - Fatchan Achyani; Imron Rosyadi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The objective of this research is to (i) identify some variables affecting compliance muzakki to throw zakat, infaq and shadaqoh ( ZIS ) and (ii) analyze optimization ZIS in strengthening community economic marginal in the research area. The analysis in this study was conducted witha descriptive-analytic approach, that describe and define the role and involvement or strategic community organizations Muhammadiyah in managing institutions amil ZIS on the very bottom of the organizational structure. The subject of this research is the PRM, the Muhammadiyah and the general public in Sukoharjo Regency. The Data that is required to achieve the objectives of this research is the primary data and secondary data obtained with the method of observation, in-depth interviews, and a search of official documents Muhammadiyah associated with the management of the institutions of the amil ZIS. Results of the first year of research further developed to produce ZIS-based management model of development branch of Muhammadiyah. data analysis with the method of focus group discussions (FGD), critical-analytical and interactive-analytic Based on the testing of regression, found that society accepter zis ( mustahik ) have not received optimal benefit because the capital exerted by institutions of amil and zakat ( laz ) has not been able to raiserevenue mustahik.While the result of the regression logistics in testing discovered that compliance or non-compliance Zakah is affected by variable commitment to the teaching of islam, orientation living infinite-dimensional akhirat, transcendental, pruden against a risk and the perception onjustice zakat.Keyword: zakah compliance; ZIS optimalization; development model